'Working in a new world': Kuhn, constructivism, and mind-dependence. (April 2015) - Massimi, Michela
Abstract: In The Structure of Scientific Revolutions, Kuhn famously advanced the claim that scientists work in a different world after a scientific revolution. Kuhn's view has been at the center of a philosophical literature that has tried to make sense of his bold claim, by listing Kuhn's view in good company with other seemingly constructivist proposals. The purpose of this paper is to take some steps towards clarifying what sort of constructivism (if any) is in fact at stake in Kuhn's view. To this end, I distinguish between two main (albeit not exclusive) notions of mind-dependence: a semantic notion and an ontological one. I point out that Kuhn's view should be understood as subscribing to a form of semantic mind-dependence, and conclude that semantic mind-dependence does not land us into any worrisome ontological mind-dependence, pace any constructivist reading of Kuhn. Highlights: In The Structure of Scientific Revolutions, Kuhn famously advanced the claim that scientists work in a different world after a scientific revolution. Kuhn's view has often been interpreted as akin to constructivism. The purpose of this paper is to take some steps towards clarifying what sort of constructivism (if any) is in fact at stake in Kuhn's view. To this end, I distinguish between two main (albeit not exclusive) notions of 'mind-dependence: a semantic notion and an ontological one. I conclude that Kuhn's view should be understood as a form of semantic 'mind-dependence, andthat semantic 'mind-dependence does not imply ontological 'mind-dependence, paceconstructivist readings of Kuhn.